Association of injurious falls with disability outcomes and nursing home admissions in community-living older persons - Gill, Thomas M; Murphy, Terrence E; Gahbauer, Evelyne A; Allore, Heather G (American journal of epidemiology, 2013)
Little is known about the deleterious effects of injurious falls relative to those of other disabling conditions or whether these effects are driven largely by hip fractures. From a cohort of 754 community-living elders of New Haven, Connecticut, we matched 122 hospitalizations for an injurious fall (59 hip-fracture and 63 other fall-related injuries) to 241 non-fall-related hospitalizations. Participants (mean age: 85.7 years) were evaluated monthly for disability in 13 activities and admission to a nursing home from 1998 to 2010. For both hip-fracture and other fall-related injuries, the disability scores were significantly greater during each of the first 6 months after hospitalization than for the non-fall-related admissions, with adjusted risk ratios at 6 months of 1.5 (95% confidence interval (CI): 1.3, 1.7) for hip fracture and 1.4 (95% CI: 1.2, 1.6) for other fall-related injuries. The likelihood of having a long-term nursing home admission was considerably greater after hospitalization for a hip fracture and other fall-related injury than for a non-fall-related reason, with adjusted odds ratios of 3.3 (95% CI: 1.3, 8.3) and 3.2 (95% CI: 1.3, 7.8), respectively. Relative to other conditions leading to hospitalization, hip-fracture and other fall-related injuries are associated with worse disability outcomes and a higher likelihood of long-term nursing home admissions.